A prospective multicentric international study on the surgical outcomes and patients' satisfaction rates of the 'sliding' technique for end‐stage Peyronie's disease with severe shortening of the penis and erectile dysfunction. (21st December 2015) - Rolle, Luigi; Falcone, Marco; Ceruti, Carlo; Timpano, Massimiliano; Sedigh, Omid; Ralph, David J.; Kuehhas, Franklin; Oderda, Marco; Preto, Mirko; Sibona, Mattia; Gillo, Arianna; Garaffa, Giulio; et al.
Abstract : Objectives: To report the results from a prospective multicentric study of patients with Peyronie's disease (PD) treated with the 'sliding' technique (ST). Patients and Methods: From June 2010 to January 2014, 28 consecutive patients affected by stable PD with severe penile shortening and end‐stage erectile dysfunction (ED) were enrolled in three European PD tertiary referral centres. The validated International Index of Erectile Function (IIEF) questionnaire, the Sexual Encounter Profile (SEP) Questions 2 and 3, and the Peyronie's disease questionnaire (PDQ) were completed preoperatively by all patients. At the follow‐up visits (at 3, 6 and 12 months), the IIEF, the SEP Questions 2 and 3, the PDQ, and the Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) were completed. The outcome analysis was focused on penile length restoration, and intra‐ and postoperative complications classified according the Clavien–Dindo Classification. Results: The mean (range) follow‐up was 37 (9–60) months. A malleable penile prosthesis (PP) was implanted in seven patients, while an inflatable three‐pieces PP was placed in the remainder. In the case of inflatable PP implantation, porcine small intestinal submucosa and acellular porcine dermal matrix were used to cover the tunical defects. While in patients undergoing malleable PP implantation, collagen‐fibrin sponge was used. The mean operative time was 145 min in the inflatable PP group and 115 min in the malleable PP group. There were no intraoperative complications. Postoperative complications included profuse bleeding requiring a blood transfusion in one patient (3.5%) on anticoagulation therapy for a mechanical heart valve (Grade II) and PP infection requiring the removal of the device (7%) (Grade III). There were no late recurrences of the shaft deformation. The postoperative functional data showed a progressive improvement in the score of all questionnaires, peaking at 12 months postoperatively. The mean (range) penile lengthening was 3.2 (2.5–4) cm and no patient reported recurrence of the curvature. Conclusions: The present series suggests that, in the hands of experienced high‐volume surgeons, penile length restoration with the use of the ST represents an effective option for end‐stage PD associated with ED and severe shortening of the shaft. Larger series and longer follow‐up will be required to fully establish the efficacy of this procedure.